To Utilize Fungal Beta-Glucan As An Encapsulating Agent For Delivery Of Probiotics - Khan, Asma Ashraf; Gani, Adil (International Journal of Food Sciences and Nutrition Innovations, 2025)
Background: Maintaining probiotic viability throughout food processing, storage, and gastrointestinal transit remains a critical limitation in the development of functional foods. Although microencapsulation is widely applied to enhance probiotic stability, the exploration of multifunctional wall materials that combine protective performance with added health benefits is still limited. Fungal β-glucans represent a promising alternative due to their structural robustness and inherent probiotic functionality.Objective: This study aimed to systematically evaluate fungal β-glucans derived from Agaricus, Pleurotus, Coprinus, and yeast as encapsulating agents for probiotic delivery, with a focus on their ability to enhance probiotic stability under storage, gastrointestinal, and thermal stress conditions.Methods: Lactobacillus plantarum, Lactobacillus brevis, and Lactobacillus casei were microencapsulated using fungal β-glucans via freeze-drying. Encapsulation efficiency, refrigerated storage stability (4 °C, 45 days), survival under simulated gastric (pH 2.0) and intestinal conditions, and thermal resistance (55–75 °C) were evaluated. Microcapsule morphology and structural interactions were analyzed using SEM, ATR-FTIR spectroscopy, and particle size analysis.Results: Encapsulation yields ranged from 63.83% to 76.63%, with Coprinus β-glucan consistently providing the highest efficiency and probiotic retention. Encapsulated probiotics exhibited significantly improved viability during storage and showed enhanced resistance to acidic, bile, and thermal stresses compared to free cells. SEM revealed porous microstructures conducive to effective cell entrapment, while ATR-FTIR confirmed molecular interactions between probiotics and β-glucan matrices.Conclusion: Fungal β-glucans, particularly those derived from Coprinus and Pleurotus, function as effective and multifunctional encapsulating materials, offering both physical protection and probiotic potential. These findings highlight fungal β-glucan-based microcapsules as a robust delivery system for probiotics, with strong prospects for application in next-generation functional foods and nutraceutical formulations.